Impact of crude oil volatility on stock returns: Evidence from Southeast Asian markets - Vu, Thanh Nam (My University, 2018)
The study investigates the connection between international oil indices and Southeast Asian stock markets. The outcomes of both employed models, namely EGARCH and GARCH-jump, confirm the significant oil-stock linkage in Southeast Asian region. While the oil price fluctuations have positive effect on stock returns, the impacts of the implied crude oil volatility index (OVX) are negative, implying that the increase in level of future oil prices uncertainty leads to downward movement on stock markets. This association is relatively stronger in crisis period and symmetric in most markets, except for Malaysia and Philippines. The research also finds a relatively weak volatility transmission from oil market to the stock returns after controlling for the impact of the implied volatility index (VIX). Additionally, the study further reports the existence of GARCH effects in Southeast Asian stock markets. Besides, the results from EGARCH models illustrate that the previously negative shocks seem to have greater effects on the current volatility of stock returns in analyzed countries than the positive shocks. Furthermore, the jump effects are found in most markets, as evidenced by the estimates for GARCH-jump models. Generally, the volatility driven by abnormal information positively affects the volatility of return while the jump behavior has negative impact on return in Southeast Asian markets. Providing greater understandings about new markets in Southeast Asian area, the research could be utilized in improving investment decisions and gaining the advantages of international portfolio diversification.
Keywords: Southeast Asia; Oil market; OVX; GARCH-jump model; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|